Cholinergic and inflammatory phenotypes in transgenic tau mouse models of Alzheimer's disease and frontotemporal lobar degeneration. Issue 1 (30th March 2020) - Cranston, Anna L; Wysocka, Adrianna; Steczkowska, Marta; Zadrożny, Maciej; Palasz, Ewelina; Harrington, Charles R; Theuring, Franz; Wischik, Claude M; Riedel, Gernot; Niewiadomska, Grazyna
Abstract: An early and sizeable loss of basal forebrain cholinergic neurons is a well-characterized feature associated with measurable deficits in spatial learning and cognitive impairment in patients with Alzheimer's disease. In addition, pro-inflammatory glial cells such as astrocytes and microglia may play a key role in the neurodegenerative cascade of Alzheimer's disease and tauopathies. We recently presented two mouse models: Line 1, expressing the truncated tau fragment identified as the core of the Alzheimer's paired helical filament, and Line 66, expressing full-length human tau carrying a double mutation (P301S and G335D). Line 1 mice have a pathology that is akin to Alzheimer's, whilst Line 66 resembles frontotemporal lobar degeneration. However, their cholinergic and inflammatory phenotypes remain elusive. We performed histological evaluation of choline acetyltransferase, acetylcholinesterase, p75 neurotrophin receptor, microglial ionized calcium binding adaptor molecule 1 and astrocytic glial fibrillary acidic protein in the basal forebrain, hippocampus and cortex of these models. A significant lowering of choline acetyltransferase-positive neurons and p75-positive neurons in the basal forebrain of Line 1 at 3, 6 and 9 months was observed in two independent studies, alongside a significant decrease in acetylcholinesterase staining in the cortex and hippocampus. The reductions in choline acetyltransferase positivity varied between 30% and 50% at an age when Line 1 mice show spatial learning impairments. Furthermore, an increase in microglial ionized calcium binding adaptor molecule 1 staining was observed in the basal forebrain, hippocampus and entorhinal cortex of Line 1 at 6 months. Line 66 mice displayed an intact cholinergic basal forebrain, and no difference in p75-positive neurons at 3 or 9 months. In addition, Line 66 exhibited significant microglial ionized calcium binding adaptor molecule 1 increase in the basal forebrain and hippocampus, suggesting a prominent neuroinflammatory profile. Increased concentrations of microglial interleukin-1β and astrocytic complement 3 were also seen in the hippocampus of both Line 1 and Line 66. The cholinergic deficit in Line 1 mice confirms the Alzheimer's disease-like phenotype in Line 1 mice, whilst Line 66 revealed no measurable change in total cholinergic expression, a phenotypic trait of frontotemporal lobar degeneration. These two transgenic lines are therefore suitable for discriminating mechanistic underpinnings between the Alzheimer's and frontotemporal lobar degeneration-like phenotypes of these mice. Abstract : We present here two tau transgenic models; L1 expressing a truncated tau fragment and L66 full-length, mutant human tau. A cholinergic deficit and region-specific inflammation in L1 mice confirms an Alzheimer's disease-like phenotype, whilst Line 66 revealed no measurable change in cholinergic expression, a phenotypic trait of frontotemporal lobar degeneration. Graphical Abstract: